Author Correction: Ctenophore relationships and their placement as the sister group to all other animals. Issue 11 (November 2017) - Whelan, Nathan; Kocot, Kevin; Moroz, Tatiana; Mukherjee, Krishanu; Williams, Peter; Paulay, Gustav; Moroz, Leonid; Halanych, Kenneth
In the version of this Article originally published the location of Punta Arenas was incorrect and should have read 'Chile' in Figures 3–5 and in the Supplementary Information. This has been corrected in all versions of the Article.